Trophic State Based On the Nygaard Index In Parit Lake in Tambang District, Kampar Regency, Riau Province. - Desi, Ria Irawan; Dahril, Tengku; Simarmata, Asmika Harnalin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACT                                            The Nygard index can be used to determine the trophic state of waters. Nygaard Index calculation is based on the number of phytoplankton species include in the following groups, that is Chlorococcales, Euglenophyceae, Centric Diatoms, Myxophyceae and Desmidiaceae. This study aims to determine the trophic status of Parit Lake based on the Nygaard Index. This research was conductedin December 2020. There were 3 station, namely at the inlet, in the middle of the lake and at the end of the lake. At each station 2 sampling points were determined at surface and Secchi. There were sampling was carried out three times, once/week. Water quality parameters measured were transparency, temperature, pH, nitrate, phosphate, dissolved oxygen, and free carbon dioxide. Result shown there were 28 types of phytplankton of Centric Diatom classes (7 types), Chloroccoles (8 types), Euglenophyceae (4 types), Cyanophyceae (2 types) and Desmidiaceae (5 types). Phytoplankton abundance ranges from 24,768-41,472Sel/ L. Water quality parameters were as follows: transparency 47.5-62 cm, temperature 31-330;, pH 5.08-5.33, nitrate 0.04-0.0437 mg / L, phosphate 0.033-0.049 mg / L, dissolved oxygen 4, 4-5.71 mg / L, free carbon dioxide from 8.48 to 10.65 mg / L. Nygaard Index value in Parit Lake during the study ranged from 2.0-2.6,or trophic state of Parit Lake can be categorized as mesotrophic to eutrophic.Keywords: Eutrophic,Mesotrophic,Oxbow lake,Phytoplankton.